Preconception Care to Improve Pregnancy Outcomes: The Science - Atrash, Hani (2020)
Introduction: In the last decades, improvements in the care of pregnancy and child development have been observed worldwide. However, pregnancy problems remain high in most countries. There was a concentration of care in the prenatal period as the primary approach for improving pregnancy results. Currently, attention to the care of pregnant women, women who have recently given birth, and newborns are focused on the care of preconception to improve the results of pregnancy and improve the outcomes of child growth and development. Objective: Describe the evidence for preconception care (PCC) and information to the health care provider, as well as describe instruments to present health care providers with PCC, its definition, its components, recommended interventions, and the scientific basis for recommendations. Methods: There was a search for published and unpublished literature related to scientific evidence for the effectiveness of PCC in improving pregnancy results. The search was carried out based on Pubmed and using data scraping techniques, in the material available on the internet and disseminated by international organizations, such as the World Health Organization and reports by government agencies. Results: It is reported that the literature on the scientific basis for PCC is fragmented, and most publications discuss evidence of one or a few interventions, with the majority of reports considering PCC for specific populations, such as women with chronic health problems and couples with infertility. However, these publications do not offer a realistic view of the proposed PCC interventions, with the scientific evidence that supports them. The general aspects of the existing literature and the recommended preconceived care interventions are described, together with the quality of the scientific evidence and the strength of the recommendations behind each of these interventions. Conclusion: Many clinical interventions have been identified that could be offered to women before conception to help avoid adverse outcomes. Most of these interventions have scientific evidence to support their role in improving pregnancy outcomes. Therefore, it is recommended that clinical care providers incorporate evidence-based prejudice services in their daily care of women of reproductive age, in an effort to improve women’s health before and during pregnancy, as well as improve pregnancy outcomes for women and their children.